Muzy w intymnym świetle. O przemianach w sztuce Odwilży i Października - Hendrykowski, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2009)
Muses in the intimate light. Transformation of Arts in the Years of “Thaw” and “Polish October 56” The study assesses the changing nature of the Polish art in the period of liberalization after Stalin’s death. It includes detailed analysis of various (social, political, philosophical and especially aesthetic) implications for important issues such as: poetry, drama, cinema, peinture, sculpture, song, popular culture etc. Marek Hendrykowski provides case studies that lead to alternative ways of viewing current conceptual frameworks of aesthetics and its consequences for interdisciplinary reflexion on arts.